Last night I sang to the monster a novel - Sáenz, Benjamin Alire 1954- (Cinco Puntos Press, 2009)
Eighteen-year-old Zach does not remember how he came to be in a treatment center for alcoholics, but through therapy and caring friends, his amnesia fades and he learns to face his past while working toward a better future